Interdisciplinary Collaboration in Infection Control: The Role of Medical Specialty Teams in Saudi Arabia - Nawaf Mohammed Alhawtan, Ali Suwailem Alotaibi, Ramzi Mohammed Althubaiti, Hatem Obaid Alzaidi, Fahad Rodaini Alshammari, Mohanad Hamad Aljehimi, Nadiah Mutlaq Almutiry (International Journal of Medical Toxicology and Legal Medicine, 2023)
Healthcare-associated infections (HAIs) present significant challenges to patient safety and healthcare quality in Saudi Arabia. Effective infection prevention and control (IPC) requires coordinated efforts across medical specialties. This article examines the current state of interdisciplinary collaboration in infection control within Saudi Arabian healthcare facilities, highlighting the roles of various specialists, existing challenges, and opportunities for improvement. Through analysis of current research and practice frameworks, this paper explores how interdisciplinary teams can effectively implement infection control measures, with specific attention to the Saudi Arabian healthcare context. The findings emphasize the importance of integrated approaches that combine specialized knowledge from different healthcare disciplines, strong leadership, effective communication, and continuous education to enhance infection control practices within Saudi healthcare institutions.